The consumption of two or more fall risk-increasing drugs rather than polypharmacy is associated with falls - Zia, A.; Kamaruzzaman, Shahrul Bahyah; Tan, Maw Pin (Wiley, 2016)
Aim: The presemt study aimed to determine the association between the risk of recurrent and injurious falls with polypharmacy, fall risk-increasing drugs (FRID) and FRID count among community-dwelling older adults. Methods: Participants (n = 202) were aged ≥65 years with two or more falls or one injurious fall in the past year, whereas controls (n = 156) included volunteers aged ≥65 years with no falls in the past year. A detailed medication history was obtained alongside demographic data. Polypharmacy was defined as “regular use of five or more prescription drugs.” FRID were identified as cardiovascular agents, central nervous system drugs, analgesics and endocrine drugs; multiple FRID were defined as two or more FRID. Multiple logistic regression analyses were used to adjust for confounders. Results: The use of non-steroidal anti-inflammatory drugs was independently associated with an increased risk of falls. Univariate analyses showed both polypharmacy (OR 2.23, 95% CI 1.39–3.56; P = 0.001) and the use of two or more FRID (OR 2.9, 95% CI 1.9–4.5; P = 0.0001) were significantly more likely amongst fallers. After adjustment for age, sex and comorbidities, blood pressure, and physical performance scores, polypharmacy was no longer associated with falls (OR 1.6, 95% CI 0.9–2.9; P = 0.102), whereas the consumption of two or more FRID remained a significant predictor for falls (OR 2.8, 95% CI 1.4–5.3; P = 0.001). Conclusions: Among high risk fallers, the use of two or more FRID was an independent risk factor for falls instead of polypharmacy. Our findings will inform clinical practice in terms of medication reviews among older adults at higher risk of falls. Future intervention studies will seek to confirm whether avoidance or withdrawal of multiple FRID reduces the risk of future falls. Geriatr Gerontol Int 2017; 17: 463–470.